2013
DOI: 10.1080/11263504.2012.736424
|View full text |Cite
|
Sign up to set email alerts
|

Pollination biology in an endangered rocky mountain toadflax (Linaria cavanillesii)

Abstract: Knowledge about the reproductive system of species inhabiting rocky habitats is scarce. The reproductive biology (floral biology, experimental pollination, insect visits, inbreeding depression, and seed predation) of the rupicolous Linaria cavanillesii was analyzed under field and experimental conditions. Self-compatibility was revealed by the high fruit set, seed set, and seed mass in the pollination experiment. Furthermore, results disclose that this species does not need insect visitors for seed production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Data on self-compatibility for Linaria species were taken from Valdés (1970), Docherty (1982), Carrió et al (2013), Voillemot et al (2018).…”
Section: Dna Extraction and Phylogenetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Data on self-compatibility for Linaria species were taken from Valdés (1970), Docherty (1982), Carrió et al (2013), Voillemot et al (2018).…”
Section: Dna Extraction and Phylogenetic Analysismentioning
confidence: 99%
“…For example, both selfing and out crossing species of the genus Senecio occur in Australian unstable habitats (Lawrence 1985). Likewise, instances of selfing have been recorded in Linaria species both in stable habitats (e.g., grasslands and rock cliffs) and in unstable habitats (e.g., sand dunes and arable land) (Carrió et al 2013). When comparing selfing rates between different populations, it was found that outcrossing predominates in areas where populations are frequently visited by pollinators, whilst in populations where visitation to flowers does not occur, selfing is the most common way to reproduce (Ness et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Based on research on one of its populations, the species was previously thought to be SC (Carrió et al. ), but populations are in fact mostly SI (with a gametophytic system). Only one fully SC population is known, although some populations show a small degree of “leaky” self‐incompatibily (Voillemot and Pannell ).…”
Section: Methodsmentioning
confidence: 99%
“…Fruits typically mature approximately 30 days after fertilization (producing between about 100 and 150 seeds maximum), and seeds are dispersed passively when capsules open. Based on research on one of its populations, the species was previously thought to be SC (Carrió et al 2013), but populations are in fact mostly SI (with a gametophytic system). Only one fully SC population is known, although some populations show a small degree of "leaky" selfincompatibily (Voillemot and Pannell 2016).…”
Section: Study Speciesmentioning
confidence: 99%
“…Grande population, where the trade-off between the seed number and the mean seed weight suggests resource limitation. However, the overall reproductive fitness of entomophilous species depends not only on the interaction with predators but also with pollinators (Östergård et al 2007;Galloni et al 2008;Carrió et al 2013). Extra flowers might also function as ovule reserve, supporting the "bet hedging hypothesis" (Stephenson 1981).…”
Section: Breeding System and Seed Predationmentioning
confidence: 97%